Tahap Preliminary Research Pengembangan Perangkat Pembelajaran Berbasis Inkuiri Terbimbing Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik SMP - Dwi Putri Amilia; Dony Permana; Edwin Musdi (Universitas PGRI Madiun, 2022)
Problem solving ability is one of the mathematical abilities that are the focus in learning mathematics. There are several factors that cause students' low mathematical problem solving abilities. One of them is the unavailability of learning tools to facilitate students in improving their mathematical problem solving skills. One of the efforts made to improve problem solving skills is to develop guided inquiry-based mathematics learning tools. This study aims to produce valid, practical, and effective learning tools. This type of research is development research with the Plomp model which consists of preliminary stages in the form of needs analysis, curriculum analysis, concept analysis, and student analysis. In the development or prototyping stage, product development is carried out, then formative evaluation is carried out to determine the validity and practicality of the product. The assessment stage is carried out by testing the practicality and effectiveness.